Molecular Response of Bacteria Exposed to Wastewater-Borne Nanoparticles - Nina Doskocz; Katarzyna Affek; Monika Załęska-Radziwiłł (Applied Sciences, 2025)
The increasing release of nanoparticles into aquatic environments, particularly via wastewater, raises concerns about their biological effects on microbial communities. This study investigated the molecular response of Pseudomonas putida to aluminum oxide nanoparticles (Al2O3NPs) under controlled conditions and in synthetic wastewater, both before and after biological treatment. Acute toxicity was evaluated using growth inhibition assays, while the expression of katE, ahpC, and ctaD—genes associated with oxidative stress and energy metabolism—was quantified via RT-qPCR. Exposure to pristine Al2O3NPs induced a strong, time-dependent upregulation of all tested genes (e.g., katE and ahpC up to 4.5-fold). In untreated wastewater, this effect persisted but at a lower intensity; bulk Al2O3 caused only moderate changes. Treated wastewater samples showed markedly reduced gene expression, indicating partial detoxification. Nanoparticles elicited stronger biological responses than their bulk counterparts, confirming the material form-specific effects. Comparative analysis with Daphnia magna revealed similar patterns of oxidative stress gene activation. These findings highlight the influence of nanoparticle form and environmental matrix on microbial responses and support the use of gene expression analysis as a sensitive biomarker for nanoparticle-induced stress in environmental risk assessment.